EVALUATION IF INTERNET BASED MATERIALS FOR LANGUAGE LEARNING - Yψηλάντη, Γ.Σ.; Γκιούρογλου , Χ.; Οικονομίδης , A. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2023)
In the past decade the use of Internet has been integrated in all aspects of human life, and has established a new era in education. In particular, in the field of foreign languages, the Web seems to be a promising delivery mechanism, as its multimedia and hypertext nature encompasses a lot of potential by integrating text, sound and video, free of charge and easily modified. Indicative of the increasing role of the Internet in language learning is the acronym Web Enhanced Language Learning (WELL), which has been added to the already long list of acronyms created to describe the use of computers in language learning. This study attempts to discuss possible applications of the Internet in language learning and further present and evaluate Web sites dedicated to English language teaching. Data has been gathered from an evaluation of 30 EFL (English as a Foreign Language) sites for the ΕΠΕΝΔΥΣΗ programme, at the University of Macedonia. The results of this work would offer a first glance opportunity to the average teacher who may be besieged by the amount of information available on-line (Net).